Effects of Intratracheal Suctioning on Hemodynamic Parameters and Arterial Oxygen - Shahram Etemadifar; Shahnaz Nemati; Yousof Aslani; Hossein ali Mehr- Alian (Iran University of Medical Sciences, 2008)
Background and Aim: Intratracheal suctioning is a standard method of nursing care for intubated patients with the aim of cleaning airway for good oxygenation. The aim of this study was to evaluate the effects of intratracheal suctioning on blood pressure, heart rate, and arterial oxygen saturation.   Materials and Methods: This was a semi-experimental research in which the patients admitted to intensive care unit of Kashani teaching center of Shahr-e-kord University in 2005. The data were collected by a questionnaire form 35 patient by observation and measurement of blood pressure, heart rate and arterial oxygen saturation.   Results: The findings showed that during suctioning, systolic pressure, diastolic pressure, and heart rate increased and arterial oxygen saturation decreased significantly, when compared with pre-suctioning period. The same occurred when these parameters were compared between pre-suctioning period and 1 minute post-suction, except for arterial oxygen saturation that had not statistically significant decline, 1 minute after suctioning. The parameters under study remained increased (including arterial oxygen saturation that decreased during suctioning) 3 minutes after suctioning, but this increase was not statistically significant when compared with pre-suctioning period. The study showed that parameters in 1 and 3 minutes after suctioning were also significantly different from those of suctioning period.   Conclusion: The finding of this research showed that the maximum changes of blood pressure and heart rate (increase) and arterial oxygen saturation (decrease) occurs during suctioning and maximum changes of blood pressure and heart rate (decrease) and arterial oxygen saturation (increase) occurs 3 minutes after suctioning. Therefore, hyper oxygenation, hemodynamic and SpO2 monitoring before, during and after suctioning are recommended.